Electronic Student Worksheets Based on Project-Based LearningIntegrated with Local Wisdom in Social Science Subjects As a Form of Implementation of Creative Pedagogy Learning in Elementary School - Siswoyo, Andika Adinanda; Wijaya, Bagus Rahmad; Efendi, Surya Fajar (UIN Sunan Kalijaga Yogyakarta, 2024)
Students' understanding of local culture is still limited, although there is actually a lot of potential for local culture that can be integrated into learning. This study aims to determine the validity and attractiveness of Electronic Students Worksheets teaching materials based on Project Learning integrated with Sumenep local wisdom in learning IPAS social studies content as a form of implementing creative pedagogy at SDN Parsanga II. This study was motivated by the lack of interesting teaching materials used in the classroom and the potential for integrating the concept of Sumenep local wisdom values in learning to present learning oriented towards students' creative behavior. This research was conducted at SDN Parsanga II, and the research subject was grade V students. This research uses the research and development (RnD) method of the 4-D model through the stages of defining, designing, developing, and distributing products. Data were collected through observation, interview, and questionnaire techniques. The results showed that the electronic student worksheets teaching material products developed were declared valid through the percentage of the average value of expert validators of 97.49% with a very valid category and the percentage of the average value of teacher and student response questionnaires of 94.96% with a very attractive category. Based on these results, it can be concluded that the Project Learning-based electronic students worksheets teaching materials integrated with local wisdom Sumenep are valid and interesting to use in helping the learning process of social studies content of cultural heritage material for grade V students of SDN Parsanga II.